Antagonistic potential of rhizosphere mycoflora against Fusarial wilt of brinjal - Akter, Romana; Hossain, KS; Bashar, MA (Dhaka University Journal of Biological Sciences, 2015)
Antagonistic potentials of seven rhizoshere soil fungi viz., Aspergillus flavus Link., A. fumigatus Fresen., A. niger Tiegh., A. terreus Thom., Penicillium sp., Trichoderma harzianum Refat. and T. viride Pers. were tested against the Fusarium oxysporum Schlecht. and F. solani (Mart.) Sacc. – the two pathogens, isolated from wilted roots of brinjal plants. Out of seven soil fungi Trichoderma harzianum was found most effective to control the growth of both the test pathogens. More than 50% inhibition of the test pathogens were observed with T. viride, Aspergillus niger and A. fumigatus in colony interaction. The maximum inhibition of radial growth of the test pathogens was observed with volatile metabolites and cell free culture filtrates of Trichoderma harzianum. This fungus may be exploited commercially to control the disease. Dhaka Univ. J. Biol. Sci. 24(2): 137-145, 2015 (July)